Utilizing Digital Media for Guidance and Counseling in Education - Suryawati, Citra Tectona; Susilo, Agus Tri; Asrowi, Asrowi; Surur, Naharus; Wijayanti, Fanny (SCAD Independent, 2025)
This causal correlational study aims to find out the effect of factors of digital technology on guidance and counseling teachers’ usage of guidance and counseling media. It involved eighty-five guidance and counseling teachers in seven regions, recruited using a convenience sampling technique. Data were garnered using the Attitude scale for digital technology developed by Emine [1], which has been considered valid and highly reliable (1.000). Data were analyzed using a linear regression test and path analysis using SPSS. The effect size of these factors varied, with the highest score observed in “technology for me” (75.1%), followed by interest in technology (70.3%), technological use (63.9%), competence (59.6%), social network (54.2%), conscious use (53.7%), recreational use (43.2%), and negative aspects (25.2%). These factors exhibited significant correlations with and influenced the usage of guidance and counseling media among guidance and counseling teachers in this study. Consequently, it is necessary to implement interventions aimed at enhancing the utilization of digital technology for guidance and counseling services.